Energy and exergy analysis of an absorption system with working pairs LiBr-H2O and Carrol-H2O at applications of cooling and heating. (December 2021) - Zheng, J.; Castro, J.; Oliva, A.; Oliet, C.
Highlights: Steady-state simulations are carried out with an air-cooled absorption system. The system are evaluated in both chiller and heat pump mode at various conditions. Two working pairs, LiBr-H2 O and Carrol-H2 O, are used in the simulations. Energy and exergy analysis are applied to the cycles. Abstract: In this work, an air-cooled, single effect solar-driven absorption system is being evaluated from the point of view of 1 st and 2 nd thermodynamic principles for two different applications: absorption chiller and heat pump. One of the most widely used working pairs, LiBr-H 2 O, is applied in this study due to its high performance in the absorption cycle. Their performance is compared with another working pair Carrol-H 2 O (Carrol contains LiBr and EG -Ethylene glycol- with a mass ratio of 4.5:1). The Carrol solution has the advantage of reducing the crystallization risk at the high concentration solution that enters the absorber. The numerical modelling was implemented on a modular object-oriented simulation platform (NEST platform tool), which allows linking different components, considered objects. In the simulations performed, the heat source temperature in the system is in the range of 70–90 ∘ C, and the inlet temperature at evaporator secondary circuit at chiller application is fixed in two values, 9 ∘ C and 14 ∘ C, and for heat pump application in 0 ∘ C and -5 ∘ C. Moreover, EG is added to the evaporator at heat pump application to prevent the refrigerant water from freezing below zero. The studied mass concentration range of EG of 10–40%. The result shows the C O P of an absorption chiller and heat pump are around 0.7 and 1.6, respectively, and the C O P EX values are 0.2-0.6 at chiller application and 0.5-1.5 at heat pump application. When compared with LiBr system, Carrol system has about 6.4% higher C O P, about 6.3% higher C O P EX, and a decrease of about 19% of cooling capacity. In the heat pump application, the heat source temperature should be lower than 90 ∘ C, and EG concentration at evaporator has been chosen as 30% as an optimal value. According to the operation condition, this EG concentration has been determined to avoid freezing in the evaporator in the studied working range. However, too much EG significantly decreases the pressure in the evaporator and increases the viscosity, hence will increase the maintenance of equipment as more vacuum tightness is required.